Transport accessibility as factor of excursion tourism development (case of Chernivtsi, Ukraine) - Roman Hyshchuk; Olexandra Pylypets' (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2016)
In the course of scientific research found that for parameterization of complex socio-economic processes with the use of transport infrastructure in tourism advisable to use transport accessibility ratio (the ratio of current and potential routes) with auxiliary coefficients movement time or distance of travel or the tourist center facility within the first. In this article was first investigated the problem of understanding the theoretical and methodological foundations and practical solution of transport accessibility of tourist and excursion objects, on the example of Chernivtsi city.